ФУҚАРОЛИК ЖАМИЯТИГА ДОИР МУМТОЗ НАЗАРИЯЛАРНИНГ РИВОЖЛАНИШИ (Scientific journal of the Fergana State University, 2023)
The article provides an overview of the development of classical theories about civil society, and provides specific solutions to the problem.